Perilaku dan Penentuan Oviposisi dari Parasitoid Telur Hadronotus leptocorisae (Hymenoptera) pada Telur Hama Bulir Padi Leptocorisa acuta (Hemiptera) - Tjandra Anggraeni; Aisah Jamili; Umrah Umrah (Biocelebes, 2010)
The research of behavior and host determination for the oviposition of egg parasitoid of Hadronotus leptocorisae on egg of the rice seed pests (Leptocorisa acuta) was carried out. H. leptocorisae collected from rice field were inserted into the tube containing of eggs of L. acuta which were divided into three group based on their ages; young eggs (0-1 days); mature eggs (2-3 days) and old eggs (4-5 days). The results showed that female H. leptocorisae prefer to oviposition on young eggs. Descriptive observation indicated that before eggs were laid, female H. leptocorisae inspect L. acuta eggs by rubbing of L. acuta eggs with its antenna and ovipositor. Furthermore, oviposition of H. leptocorisae eggs was begun by holing of L. acuta eggs and was followed by putting its eggs by its ovipositor. That behavior is its strategies to survive. The results of this study can contribute to answer pest L. acuta problems which are often found in rice fields. By the appropriate monitoring of L. acuta eggs in rice field, the disposal time of H. leptocorisae could be done effectively and efficiently.Key words: Hadronous leptocorisae; Leptocorisa acuta; egg parasitoid.